2013
DOI: 10.5194/acp-13-10143-2013
|View full text |Cite
|
Sign up to set email alerts
|

Cloud-resolving simulations of mercury scavenging and deposition in thunderstorms

Abstract: Abstract. This study examines dynamical and microphysical features of convective clouds that affect mercury (Hg) wet scavenging and concentrations in rainfall. Using idealized numerical model simulations in the Regional Atmospheric Modeling System (RAMS), we diagnose vertical transport and scavenging of soluble Hg species -gaseous oxidized mercury (GOM) and particle-bound mercury (HgP), collectively Hg(II) -in thunderstorms under typical environmental conditions found in the Northeast and Southeast United Stat… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
23
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 51 publications
2
23
0
Order By: Relevance
“…These reactions modify the Hg(II) source particularly in the lower FT (a factor of 20; SI Appendix and Fig. S10), where Hg(II) is more susceptible to dry (51) and wet deposition (52). Our study indicates that atmospheric mercury is a rather chemically dynamic component of air that warrants future study.…”
Section: Atmospheric Implicationsmentioning
confidence: 75%
“…These reactions modify the Hg(II) source particularly in the lower FT (a factor of 20; SI Appendix and Fig. S10), where Hg(II) is more susceptible to dry (51) and wet deposition (52). Our study indicates that atmospheric mercury is a rather chemically dynamic component of air that warrants future study.…”
Section: Atmospheric Implicationsmentioning
confidence: 75%
“…For example, fluxes at Naval Air Station Pensacola Outlying Landing Field (OLF) in Florida were 17.1 µg m −2 in 2012 and 21.0 µg m −2 in 2014 (MDN, 2014). A contributing factor to wet deposition in the Gulf Coast area may be related to high atmospheric convection during thunderstorms and scavenging of gaseous oxidized Hg (GOM) from the free troposphere (Nair et al, 2013), as well as down-mixing of air with high GOM from the free troposphere .…”
Section: Introductionmentioning
confidence: 99%
“…The high deposition levels experienced in the SE US cannot be explained by regional anthropogenic sources of mercury alone, which are mainly located within the Ohio River valley, where the prevailing winds carry emissions northeast. Additionally, several modeling studies Nair et al, 2013) have shown that meteorological patterns above the SE US greatly influence the wet deposition of mercury and that these processes are linked with deep convective activity. This indicates that a regional emission-deposition pattern is most likely not the major source-receptor relationship for mercury entering the environment over Florida, in the SE US, meaning that other possibilities, such as enhanced atmospheric oxidation followed by deposition, need to be explored.…”
Section: Atmospheric Hg In the Southeastern Usmentioning
confidence: 99%
“…The rapid oxidation of mercury in the lower FT is of potential relevance in the SE US, where there have been several studies linking deep convective activity to the elevated levels of mercury found in rainwater (Guentzel et al, 2001;Landing et al, 2010;Nair et al, 2013). The bioaccumulation of methyl mercury in fish tissues is particularly relevant in this region, where it has been deemed unsafe to eat fish harvested from many lakes in the region (Engle et al, 2008;Liu et al, 2008).…”
Section: Atmospheric Implicationsmentioning
confidence: 99%